(untitled) (Journal of Nepal Geological Society, 2009)
Nepal lies at the collision zone between the Indian subcontinent and the Tibetan Plateau of the Eurasian continent. It is made up of enormous tectonic stacking of sedimentary and metamorphic rocks with granite intrusions that resulted from the collision and under-plating of the Indian Craton with the Lhasa block of Tibet. The five major tectonic zones separated from each other by thrust contacts from south to north are the Terai, Siwalik or Sub Himalaya, Lesser Himalaya, Higher Himalaya and Tibetan Tethys. On the northern margin of the Indian subcontinent, foreland sedimentary basins began to develop immediately after the terminal collision between the northward drifting Indian Plate and relatively passive Eurasian Plate in Late Eocene time. The southern part of Nepal known as the Terai and Siwalik foothill, lies in the northern margin of the Ganga Basin and Purnea Basin that extend from India. Such basins with thick accumulation of sediments are considered as the potential area for petroleum exploration. Regional scale seismic reflection, gravity and magnetic data combined with surface mapping and basin analysis have established the subsurface framework of southern Nepal. Geological settings potential for hydrocarbon prospects recognized in Nepal include structural traps related to normal faulting involving pre-Siwalik formation and thrusting involving Siwaliks, structural traps associated with frontal blind thrusts, anticlines and thrust-faults, basement controlled structures and stratigraphic pinchouts. Drilling data consists of only one well drilled in the eastern part of Nepal. Oil and gas seeps have been observed in Dailekh area emanating through deep faults. Geochemical analyses of these seep samples indicate that these oil and gas have geologic origin from mature source rocks. Various outcrop samples from different parts of the country have been found rich in organic carbon. Source-rock maturity basin modeling constructed for various sections indicates that the level of thermal maturity is within oil and gas generating window. The Potwar Basin to the west in Pakistan and Assam Basin to the east in India having similar geologic setting to that of Nepal are producing oil and gas for a long time. In the Indo-Gangetic Plain across the border on Indian side, many deep wells have recorded the presence of gas and high content of organic carbon. Assessment of the available data acquired so far indicate that there is a fairly good possibility of discovering petroleum resource in Nepal.